Systematic review of lithium extraction from salt-lake brines via precipitation approaches - Zhang, Ye; Hu, Yuehua; Wang, Li; Sun, Wei (Minerals engineering, 2019)
•Precipitation approaches are widely used to extract lithium from salt lake brines.•Promising magnesium precipitation technology for comprehensively utilizing Li and Mg.•Future research needs on lithium extraction are discussed. Lithium is one of the most important raw materials for the production of glass, ceramics, nuclear materials, pharmaceuticals, and batteries. Almost 80% of total land-based lithium reserves globally are salt-lake brines. Therefore, lithium should be extracted from salt-lake brines to meet the demand of various industries for lithium resources. Several approaches for lithium extraction have been developed in the past few decades, such as precipitation, ion exchange, adsorption, solvent extraction, and electrolysis. Among these methods, precipitation is the earliest studied and utilized in industrial plants. Furthermore, it has several advantages, such as low cost, green principle, and easy industrialization. This paper reviews the precipitation technology for lithium extraction and the relative mechanism proposed in literature to identify its important parameters. Precipitant dosage, pH value, temperature, and particle size of precipitate are important factors in the process. Economic viability and green principle of various methods are discussed, and potential technologies are suggested. Novel magnesium precipitants appear to be a prospective technology for lithium extraction from brines with high Mg/Li mass ratios. Magnesium precipitation technology also shows great potential in the comprehensive utilization of lithium and magnesium resources. Various precipitation approaches for lithium extraction from brines and perspectives for further investigation are proposed.